Regulation of glucose uptake in mammalian cells by protein phosphorylation networks - Henrique, Andreia (2022)
Tese de doutoramento em Biologia (Biologia de Sistemas), apresentada à Faculdade de Ciências da Universidade de Lisboa, 2019.